A CLOSER LOOK ON DISCOURSE ANALYSIS BY USING SPEECH ACT THEORY AND HALLIDAYAN COHESION - Nabila Firda Asy'ari (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2018)
This paper will describe and look out what actually speech act theory and Hallidayan cohesion in order to analyze a discourse. Here, the main point that we want to analyze is the spoken discourse. We will open up what happens if we use speech act theory to analyze a discourse and what will happen if we use Hallidayan cohesion in order to analyze a discourse. We will know which one of these are the best or suitable to apply while analyzing a discourse. Is it speech act theory or Hallidayan cohesion? Then, in conclusion, we will also know why speech act theory is the best approach to analyze a discourse, especially spoken discourse.